2021
DOI: 10.3390/bioengineering8120198
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Magnetite and Bioelectrochemical Systems on Anaerobic Digestion

Abstract: Conventionally, the anaerobic digestion of industrial effluent to biogas constitutes less than 65% methane, which warrants its potential methanation to mitigate carbon dioxide and other anthropogenic gas emissions. The performance of the anaerobic digestion process can be enhanced by improving biochemical activities. The aim of this study was to examine the synergistic effect of the magnetite and bioelectrochemical systems (BES) on anaerobic digestion by comparing four digesters, namely a microbial fuel cell (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…It was found that the MEC had the highest removal values for COD (98.6%), TOC (95.9%), TSS (88.4%), phosphate (76.3%), and NH 3 -N (43.7%). This can be attributed to the higher electron recovery efficiencies of the MEC system, namely the maximum current density (23.3 mA/m 2 ), coulombic efficiency (110.4%), and electrical conductivity (180 µS/cm) [ 22 , 23 , 48 , 49 ]. Conversely, exposure to electromagnetism (the ES) resulted in better removal of color (97.9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the MEC had the highest removal values for COD (98.6%), TOC (95.9%), TSS (88.4%), phosphate (76.3%), and NH 3 -N (43.7%). This can be attributed to the higher electron recovery efficiencies of the MEC system, namely the maximum current density (23.3 mA/m 2 ), coulombic efficiency (110.4%), and electrical conductivity (180 µS/cm) [ 22 , 23 , 48 , 49 ]. Conversely, exposure to electromagnetism (the ES) resulted in better removal of color (97.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Bioelectrochemical systems (the MFC and the MEC) and electromagnetic systems are the most-used electromagnetic field systems in anaerobic digestion [ 21 , 22 ]. Madondo et al [ 23 ] reported that the most promising bioelectrochemical system is the MEC with 79.1% CH4 removal and 91.6% COD removal from sewage sludge. The MEC was also better in terms of electrochemical measurements, with a maximum current density of 23.3 mA/m 2 , an electrochemical methane yield of 153.44%, and a heterotrophic methane yield of 123.48%, and electrical conductivity of 269.7 µS/cm.…”
Section: Introductionmentioning
confidence: 99%
“…Electro-activity of the microbial community has been regarded as the indicator to evaluate the EET of microbial aggregates. 16 The increase in the sludge electro-activity has been extensively reported in the EET-related processes including BESs, 17 direct interspecies electron transfer, 18 Feammox, 19 and so forth. The similarity of these systems is that the conductivity and capacitance of microbial aggregates were frequently found to increase with the operation.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, variations in the AD process feedstock and environmental conditions can result in high complex sludge that is difficult to treat economically and environmentally [9,12,19]. On this basis, our previous work [17,20,21] and other researched studies [9,12,18,19,[22][23][24] show that using a photocatalyst (Fe-TiO 2 ) with magnetic properties has tremendous potential in wastewater settings. With this, and the need to meet future water demands, creating a cost-effective, user-friendly and reliable technology with a significant impact on energy production and recuperation in water settings is urgently needed [3,5,15,16].…”
Section: Introductionmentioning
confidence: 96%